The Historical Roots of Autonomy in Nicaragua's Caribbean Coast: From British Colonialism to Indigenous Autonomy. (July 2016) - BARACCO, LUCIANO
Abstract : This article reviews historical forms of localised government on Nicaragua's Caribbean coast and contrasts them with the contemporary struggle to attain a communal form of autonomy undertaken by the region's indigenous population. It suggests that the contemporary autonomy process shares few features with the historical precedents of localised government which are commonly invoked to legitimise it. Instead, its roots can be located in the emergence of a Moskitian nationalism amongst the Miskitu which occurred to counter the assimilating impulse of an increasingly developmentally determined national state during the 1960s under the Somoza dictatorship, and then more thoroughly during the Sandinista revolution.